Life Skills and Adolescent Mental Health Can Kids Be Taught to Master Life? - Madsen, Ole Jacob (Routledge Focus on Mental Health, 2023)
Can school teach us to master life? This book confronts what the author sees as an ongoing trend in many Western democracies where citizens are increasingly being held accountable for their health and happiness. The author believes that the introduction of life skills in school shows a tendency to place more responsibility on the individual rather than address fundamental societal flaws that really should be solved politically. It examines how such responsibility to psychologically deal with these problems affects our mental health and quality of life. This book questions the fundamentals of the life mastery curriculum where we might be risking the creation of just another arena where children have to perform, challenging readers to evaluate more closely the premises, consequences and limitations of life mastery. The book, one of the first to question 'life mastery' as an achievable goal with critical reviews of the 21st century skills movement, will be of interest to psychologists, school counsellors, teachers, students, politicians, and any reader evaluating school curriculums in relation to the decline in youth and adolescent mental health.